The Influence of Learning Motivation and Parental Attention on Biology Learning Outcomes of Students at State High School 1, Komodo District, West Manggarai Regency - Amandus, Valerianus; Ihsan, Ikhlashul; Fiqrillah, Siti Khumairah (International Journal of Education, Information Technology, and Others, 2025)
This research aims to determine the influence of learning motivation and parental attention on the biology learning outcomes of science class students at Komodo State High School. This type of ex-post facto research is quantitative descriptive. The independent variables in this research are learning motivation (X1), parental attention (X2) while the dependent variable is learning outcomes (Y). The sample for this research was 206 students in class X and XI Science at SMA Negeri 1 Komodo using a supportive random sampling technique. This research was carried out in August - September 2024. The research data was obtained using a questionnaire on learning motivation and parental attention. The data analysis technique is analysis (descriptive statistics) with the help of the SPSS (Statistical Package for Social Science) version 25 for Windows program. Based on the results of inferential statistical analysis, a significance value of 0.000 <0.05 was obtained. It can be concluded that learning motivation and parental attention have a positive and significant effect on the biology learning outcomes of class X and XI IPA students at SMA Negeri 1 Komodo.